Analisis Faktor yang Memengaruhi Pemilihan Tempat Persalinan Ibu Hamil di Wilayah Kerja Puskesmas Lasusua Kabupaten Kolaka Utara Tahun 2021 - Ferawati; Rahmawati Azis; Muhammad Syafar (2022)
Utilization of mothers giving birth in health facilities is very important, especially in preventing unwanted events during childbirth. The purpose of the study was to analyze the factors that influence the choice of place of delivery for pregnant women in the work area of the Lasusua Public Health Center, North Kolaka Regency. The type of research used is analytic survey research with a